The image of a snake in the tales of the Altaians: ulu ‘snake-dragon’, ker-jutpa ‘chestnut swallowed’, jek-jylan ‘snake-eater’, jylan ‘snake’, moыys ‘monster-hero’, Abram-moos - S. B. Sarbasheva (Nomadic Civilization: Historical Research)
The image of the snake is one of the most common characters in the mythology of the peoples of the world. This image is also quite widely represented in the oral folk art of the Turkic-Mongolian peoples, has a variety of interpretations in its various genres. In this article, the author refers to the image of the snake as a tabooed sacred character in the folklore of the Altaians. In the popular consciousness, the snake was a sacred, especially revered creature. Altaians have a number of folk customs and beliefs associated with this reptile. As a result of the conducted research, the functions of the snake in the signs were determined, the interconnectedness and interchangeability of the functions of this sacred reptile were revealed. Of particular interest is the recoding of the snake image in different semiotic systems.